Pengaruh Service Excellent Petugas Ground Handling Terhadap Kepuasan Penumpang pada Bandar Udara Sultan Babullah Ternate - Olivia Oya; Suprapti (Jurnal Multidisiplin Madani, 2022)
This study aims to see how the influence of service excellent ground handling officers on passenger satisfaction at Sultan Babullah Airport, Ternate. The sampling technique in this study is a probability sampling technique with a simple random sampling method, the number of samples obtained is 100 respondents. Data were collected using a questionnaire with the analytical methods used, namely validity test, reliability test, simple linear regression test, and t test (partial). The results of the simple linear regression test show that there is a unidirectional effect, which means that service excellent has a positive effect on passenger satisfaction. The results of the t-test show that the significance value is <0.05 and the tcount > ttable value. This shows that Ho is rejected and Ha is accepted. The results of the study concluded that service excellent had a significant effect on passenger satisfaction at Sultan Babullah Airport, Ternate.